2006
DOI: 10.20467/1091-5710.10.1.49
|View full text |Cite
|
Sign up to set email alerts
|

The Caring Behaviors Inventory for Elders: Development and Psychometric Characteristics

Abstract: The purpose of this study was to develop the Caring Behaviors Inventory for Elders (CBI-E) and to establish its psychometric characteristics further. The 28-item CBI-E was framed by Watson’s theory of human caring. Aconvenience sample (N = 215) of elders and their caregivers (N = 138) completed the instrument. Psychometric analysis included item analysis, test-retest reliability, internal consistency reliability with Cronbach’s alpha coefficients, contrasted groups construct validity, and factorial validity, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(49 citation statements)
references
References 0 publications
2
40
0
7
Order By: Relevance
“…Watson, in support of the theory, argued that "if human caring-healing is not sustained as part of our collective values, knowledge, practices, and global mission, the survival of humankind is threatened" (1996, p. 147). The Caring Behaviors Inventory-Elders (CBI-E) used to measure caring in this study was directly derived from the Theory of Human Caring and stresses the interaction of nurses and patients in therapeutic relationships (Fawcett, 2005;Wolf et al, 2004;Wolf, Zuzelo, Goldberg, Crothers, & Jacobson, 2006).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Watson, in support of the theory, argued that "if human caring-healing is not sustained as part of our collective values, knowledge, practices, and global mission, the survival of humankind is threatened" (1996, p. 147). The Caring Behaviors Inventory-Elders (CBI-E) used to measure caring in this study was directly derived from the Theory of Human Caring and stresses the interaction of nurses and patients in therapeutic relationships (Fawcett, 2005;Wolf et al, 2004;Wolf, Zuzelo, Goldberg, Crothers, & Jacobson, 2006).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The CBI-E was developed by Wolf et al (2004Wolf et al ( , 2006 to measure perceptions of nurse caring reported by older individuals and the nurses caring for them. Several versions of the CBI exist.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies of caring are required, aimed at establishing the association between patients' perceptions of caring and the satisfaction with care outcome (115), as well as of caring as a quality indicator The lived experience of caring is an area for further investigation. Research is needed to illuminate which health care professionals, organizational and social factors shape perceptions and behaviors of caring and how this occurs (105) Future studies on developing a conceptual framework for documentation that is capable of recording caring values, problem solving and patient satisfaction are highly recommended And finally, further studies are recommended to preserve and develop caring in the health care organization of today.…”
Section: Thereforementioning
confidence: 99%